Antígenos para a produção de soro contra o Veneno do escorpião Tityus serrulatus - Thais Melo Mendes (2007)
Scorpions are animals that use venom to capture preys and to defendthemselves. These venoms possess toxins that act in ionic channels of many organisms. Some poisons are very toxic for mammals, including man, and may cause death. In Brazil, there are some species of scorpions dangerous to human health and there is a great concern relative to accidents. Since the decade of 60, researchers are studying scorpion venom. Although already exist an effective anti-scorpionic serum, problems in its production and use still exist. Therefore, for the development of a better quality serum or even a vaccine, it is necessary a greater knowledge of the venom composition and action. Our group is involved in the search of new imunogens for anti-venom production. To achieve such purpose, a search for new toxins in a cDNA library of Tityus serrulatus venom gland was carried out. As result several nucleotidesequences coding for toxin-like proteins were identified. cDNAs of two main toxins of the T. serrulatus venom, TsTx and TsTx-I, were obtained and used with the cDNA of TsNTxP, in the constructions of expression cassettes. These were constructed by insertion into a plasmidial vector of copies of genes in series (in tandem) or a copy of different genes, encoding proteins different (chimera). Two constructions were used for bacterial expression assays and the obtained recombinant proteins inoculated in animals, for antibodies production. The antibodies were tested and neutralized the toxic effects of the T. serrulatus crude venom. The results obtained in this work open new possibilities for theproduction of anti-scorpionic serum using the recombinant proteins described here as antigen. The most important advancement was obtained to determine the ability of the recombinant toxin TsTx - I to produce antibodies with the power to neutralize the Tityus serrulatus venom since it had not yet studies in this area with this toxin.